A Novel 1.0 Mb Duplication of Chromosome 8p22-21.3 in a Patient With Autism Spectrum Disorder. Issue 2 (April 2015) - Dong, Ping; Xu, Qiong; An, Yu; Zhou, Bing-Rui; Lu, Ping; Liu, Ren-Chao; Xu, Xiu
Autism spectrum disorders are a group of neurodevelopmental disorders with a strong genetic etiology. Cytogenetic abnormalities have been detected in 5% to 10% of the patients with autism spectrum disorders. In this study, the authors present the clinical and array-based comparative genomic hybridization evaluation of a 4-year-old male with autism spectrum disorder and mental retardation. The patient was found to carry a de novo duplication of chromosome 8p22-21.3 of 1.0 Mb as ascertained by quantitative polymerase chain reaction, and this region encompassed 3 genes including Pleckstrin and Sec7 domains-containing protein 3 (PSD3), SH2 domain-containing 4A (SH2D4A), and Chondroitin Sulfate N-Acetylgalactosaminyltransferase 1 (CSGALNACT1) . This represents the smallest rearrangement of chromosome 8p as yet found in a patient with autism spectrum disorder, but the significance of this mutation is still ambiguous.